Evidence of the use of the Perme Intensive Care Unit Mobility Score in hospitalized adults: a scoping review - Maria Helena Lenard; Clovis Cechinel; Tissiane Bona Zomer; João Alberto Martins Rodrigues; Maria Angélica Binotto; Rossana Spoladore (Revista Latino-Americana de Enfermagem)
Objective: to map the scientific literature regarding the use of the Perme Intensive Care Unit Mobility Score in hospitalized adults. Method: scoping review, structured according to the methodological guidelines of the Joanna Briggs Institute - Evidence Synthesis Groups, with searches in seven databases and gray literature. The studies were selected by two reviewers, using an instrument for data extraction. Results: the analysis of the 29 selected studies showed a predominance of longitudinal studies (34.48%), conducted in Brazil (48.27%) in Intensive Care Units (29%), and published between 2020 and 2021 (48.24%). The studies demonstrated the use of the Perme Score for description and reliability of the instrument, translation and cultural adaptation, association between functional mobility, clinical characteristics and outcomes, mobility assessment after interventions, mobility assessment and potential barriers to mobilization, and use of the score for validation of other instruments and various clinical profiles. Conclusion: the Perme Score is an instrument capable of measuring physical mobility, including possible barriers to mobility, with potential for use in scenarios outside the Intensive Care Unit, in intervention studies for early mobilization and prediction of hospitalization outcomes.